2012
DOI: 10.1007/s00737-012-0288-9
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychosocial determinants of treatment outcome for mood and anxiety disorders up to 8 months postpartum

Abstract: Little is known about the biopsychosocial determinants that predict postpartum treatment outcome for mood and anxiety disorders. Postpartum mood and anxiety symptoms and psychosocial/biological variables were recorded for 8 months of 22 women treated with antidepressants during pregnancy. Depression scores decreased by 58%, whereas anxiety scores decreased by 35%. Family history of psychiatric illness and prior psychiatric illness unrelated to pregnancy predicted depressive treatment outcome, and sexual abuse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(16 reference statements)
0
0
1
Order By: Relevance
“…Earlier studies found that prior psychiatric illness predicted treatment outcomes in postpartum depressed/anxious women. 41,42 Our findings, which are different, could be due to underreporting of psychiatric history by mothers during their initial assessment. Due to fear of stigma, acceptance of psychiatric illness after a baby's birth can be distressing and shameful.…”
Section: Discussioncontrasting
confidence: 78%
“…Earlier studies found that prior psychiatric illness predicted treatment outcomes in postpartum depressed/anxious women. 41,42 Our findings, which are different, could be due to underreporting of psychiatric history by mothers during their initial assessment. Due to fear of stigma, acceptance of psychiatric illness after a baby's birth can be distressing and shameful.…”
Section: Discussioncontrasting
confidence: 78%